Use of Platelet‐Rich Fibrin Membrane as a Palatal Bandage. Issue 4 (1st November 2014) - Aravindaksha, Shyam Prasad; Batra, Puneet; Sood, Vishal; Kumar, Ashish; Gupta, Geeti
Abstract : Introduction : Free gingival grafting is one of the most common techniques used to increase the dimensions of keratinized tissue (KT). The palatal donor sites heal with secondary intention, require a longer time, and cause discomfort to patients. This case series describes the use of platelet‐rich fibrin (PRF) membrane as a palatal bandage to cover donor sites. To the best of the authors' knowledge, this is the first report that describes the use of PRF membrane as a palatal bandage. Case Series: Five patients requiring augmentation of KT are described in this case series. The palatal donor sites of four of these patients were covered with PRF membranes as a palatal bandage. The donor site of the fifth patient was allowed to heal in a conventional way without PRF membrane to evaluate the difference in healing. The healing was evaluated visually by hydrogen peroxide test at days 12, 13, 18, 19, 24, 25, 30, and 31. Palatal donor sites covered with PRF membranes demonstrated considerably faster healing compared with the site not covered by PRF membrane. Conclusions: The superior healing observed at the PRF membrane sites supports its use in accelerating soft‐tissue healing. PRF membrane as a palatal bandage is an efficacious approach to protect the raw wound area of a palatal donor site to reduce healing time and patient discomfort.